2016
DOI: 10.1016/j.enbuild.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Keeping California cool: Recent cool community developments

Abstract: a b s t r a c tIn 2006, California introduced the Global Warming Solutions Act (Assembly Bill 32), which requires the state to reduce greenhouse gas emissions to 1990 levels by 2020. "Cool community" strategies, including cool roofs, cool pavements, cool walls and urban vegetation, have been identified as voluntary measures with potential to reduce statewide emissions. In addition, cool community strategies provide co-benefits for residents of California, such as reduced utility bills, improved air quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 3 publications
0
17
0
1
Order By: Relevance
“…This study examined one potential trade-off between land surface temperature and T MRT . Other potential cool pavement tradeoffs to consider include increased reflected UV radiation (Epstein et al 2017), daytime glare versus nighttime visibility, low upfront installation costs versus maintenance costs as materials degrade, and environmental impact over the material lifecycle (Gilbert et al 2016.…”
Section: Sun Valleymentioning
confidence: 99%
See 2 more Smart Citations
“…This study examined one potential trade-off between land surface temperature and T MRT . Other potential cool pavement tradeoffs to consider include increased reflected UV radiation (Epstein et al 2017), daytime glare versus nighttime visibility, low upfront installation costs versus maintenance costs as materials degrade, and environmental impact over the material lifecycle (Gilbert et al 2016.…”
Section: Sun Valleymentioning
confidence: 99%
“…Field studies, lab experiments, and modeling studies that focus on solar reflective coating and proxy materials have confirmed surface temperature reductions of pavements and roofs via albedo increases (Synnefa et al 2011, Carnielo and Zinzi 2013, Santamouris 2013, Georgescu et al 2014. Many authors have called for promotion of solar reflective coatings on pavement in roads, parking lots, and school play yards (Rosenfeld et al 1998, Akbari and Matthews 2012, Gilbert et al 2016. To mitigate the UHI, municipalities in the United States have increasingly explored the use of solar reflective coatings (Estrada et al 2017, Gilbert et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these strategies, cool roofs have received much research attention due to the notable thermal benefits. Continuous monitoring and simulation studies have been involved to evaluate the impacts of cool roofs on surface and air temperature, the number and frequency of extreme weather conditions, energy consumptions and GHG emissions [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this reduction, but also the UHI effect and thereby co-benefits for residents (such as reduced utility bills, improved air quality and health, fortified climate resilience,), "cool community" strategies including cool roofs, cool pavements, cool walls and urban vegetation, have been identified as voluntary measures. Lawrence Berkeley National Laboratory (LBNL), which worked with state and local stakeholders (officials, non-profit organizations, school districts, utilities and manufacturers) in a recent study, observed that the recipe for success of cool community efforts includes empowered leadership, broad stakeholder backing, support of other policy objectives, and guidance from researchers to ensure sound implementation of promising science (Gilbert, Mandel, & Levinson, 2014). Mitigation and adaptation solutions to climate change exist, real experiences feedbacks exist, scientific understanding of the phenomena is well developed and National Plans are deployed as in France or California.…”
Section: Introductionmentioning
confidence: 98%